Wastewater treatment by coagulatıon wıth countercurrent sludge return - Alekseev, E. V. (Revista de la Universidad del Zulia, 2020)
Industrial wastewater contains pollutants that do not oxidize under the biological wastewater treatment conditions of populated areas. The treatment of wastewater containing persistent organic substances can be effective in its extraction. Using only water treatment separation methods does not provide sufficient efficiency. Significantly better results are obtained by combining the persistent organic pollutant coagulation method with subsequent separation processes. The disadvantage of coagulation is the need to use large doses of reagents and a large number of wastewater treatment processes. The objective of the research was to determine the possibility of reducing the doses of mineral coagulants and related reagents while maintaining sufficient efficiency in the treatment of contaminant water by countercurrent transfer of the solid phase of the sludge to the previous separation stages. . For the experimental investigation, a facility was used, which included a three-section block of sedimentation chambers, equipment for the manufacture and dosage of reagents, devices for pumping sludge and water sampling. The research was carried out in aqueous solutions of contaminants: persistent synthetic dyes used in the textile industry. The concentration of the dye solutions was assumed to be constant, equal to 150 mg / l. Three series of experiments were carried out with different conditions to dose the coagulant and return the hydroxyl mud. The results of the experiments were analyzed using the Langmuir adsorption equation and the graphical constructions of the equilibrium and the lines of work of the contaminant extraction process. Compared to the traditional single-stage coagulation scheme, which includes a single addition of reagents without reusing the sludge, the use of solid-phase countercurrent transfer coagulation schemes was found, based on the research results. of sludge conductors gives a significant reduction in the number of reagents consumed and, consequently, a decrease in the amount of sludge removed.